Patterning of Nanocrystalline Cellulose Gel Phase by Electrodissolution of a Metallic Electrode - Jean-Michel Daignan (572645) (2014)
At high concentration or in the presence of electrolytes and organic solvents, solutions of cellulose nanocrystals (CNCs) can form gels exhibiting optical properties similar to the ones of liquid crystal phases. In an attempt to pattern such a gel phase, we have studied the electrodissolution of a metallic electrode in a water suspension of carboxylated CNCs (cCNCs). Depending on the metal used, the electrodissolution process was observed at a different positive potential. In the case of copper the minimum potential at which we could observe optically the growth of the gel phase was 200 mV. The growth rate was current limited indicating that the process was controlled by the electrodissolution of the copper electrode. This hypothesis was confirmed by using circular and square copper patterns as positive electrodes. In both cases, the consumption of the electrode material was observed optically and correlated with the growth of the gel phase. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1371/journal.pone.0099202